A robust audio watermarking scheme based on lifting wavelet transform and singular value decomposition - Lei, Baiying. (2013)
In this paper, a new and robust audio watermarking scheme based on lifting wavelet transform (LWT) and singular value decomposition (SVD) is proposed. Specifically, the watermark data is efficiently inserted in the coefficients of the LWT low frequency subband taking advantage of both SVD and quantization index modulation (QIM). The use of QIM renders our scheme blind in nature. Furthermore, the synchronization code technique is also integrated into our hybrid LWT–SVD audio watermarking method. Experimental and analysis results demonstrate that the proposed LWT–SVD method is not only robust against both general signal processing attacks and desynchronization attacks but also achieve a very good tradeoff between robustness, imperceptibility and payload. Comparisons with the typical and related audio watermarking algorithms also show that our proposed method outperforms most of the selected algorithms.